2021
DOI: 10.2355/tetsutohagane.tetsu-2021-068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solute Carbon on the Evaluation of Dislocation Density in as Quenched Martensite by X-ray Diffraction

Abstract: X-ray diffraction analysis is one of powerful tools on the dislocation analysis and this method can be applied reasonably for many metals with isotropic crystal structure such as bcc and fcc. In this study, modified Williamson-Hall analysis was applied for martensitic steels containing 0.006 -0.26 mass% carbon and proved that the value of dislocation density increases with increasing the carbon content. However, martensitic steels containing solute carbon have bct structure characterized by different lattice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is generally known that the dislocation density (N dis ) in lath martensite increases with increasing C total . 2,3) Figure 5 shows N dis in the as-quenched specimens estimated by the mWH/WA method (solid circle) against previously reported values. 2,11) N dis increased with an increase in C total ; however, the difference between the 0.3C and 0.6C steels was as small as approximately 0.3 × 10 15 m − 2 .…”
Section: Hardness and Microstructure In As-quenched Martensitic Steelmentioning
confidence: 79%
See 2 more Smart Citations
“…It is generally known that the dislocation density (N dis ) in lath martensite increases with increasing C total . 2,3) Figure 5 shows N dis in the as-quenched specimens estimated by the mWH/WA method (solid circle) against previously reported values. 2,11) N dis increased with an increase in C total ; however, the difference between the 0.3C and 0.6C steels was as small as approximately 0.3 × 10 15 m − 2 .…”
Section: Hardness and Microstructure In As-quenched Martensitic Steelmentioning
confidence: 79%
“…2,11) N dis increased with an increase in C total ; however, the difference between the 0.3C and 0.6C steels was as small as approximately 0.3 × 10 15 m − 2 . Takaki et al 2) reported that N dis becomes almost constant over 0.14 mass% of C total in lath martensite, which is in accordance with the results of this study.…”
Section: Hardness and Microstructure In As-quenched Martensitic Steelmentioning
confidence: 88%
See 1 more Smart Citation